ARE ALL LOYAL CUSTOMERS CONSCIOUS? AN EMPIRICAL STUDY ON CUSTOMER LOYALTY DISCUSSIONS IN THE CONTEXT OF CONSCIOUSNESS - Akin, Eyup (European Scientific Journal, ESJ, 2012)
Although the remark/opinion/assumption that loyalty is conscious is frequently observed in articles dealing with marketing and customer behaviors, there is only a limited number of studies attempting to clarify this matter. This study, which bears an empirical character, has been grounded on the presumption that the opinion that loyalty is always conscious may be paradoxical and conducted to ascertain that loyalty may be unconscious, as well. Based on the resultant findings reached at the end of the analysis of data obtained through survey, it has been found that customers may be grouped into such categories as conscious loyals, unconscious loyals, conscious disloyals and unconscious loyals. Practical suggestions have been drawn for enterprises based on predictions and projections for the characteristics of consumers to be included in these groups, identified at the conclusion part of the study.